2016
DOI: 10.1186/s12883-016-0706-0
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-synuclein measured in cerebrospinal fluid from patients with Alzheimer’s disease, mild cognitive impairment, or healthy controls: a two year follow-up study

Abstract: Backgroundα-Synuclein has been proposed as a potential biomarker for Alzheimer’s disease (AD) and amnestic mild cognitive impairment (aMCI). However, results from α-synuclein measurements in cerebrospinal fluid (CSF) have been inconclusive, and to our knowledge, longitudinal studies of changes prior to the AD diagnosis have not been investigated.MethodsLevels of α-synuclein at baseline and after one and two years were measured in CSF, by enzyme-linked immunosorbent assay. Twenty-six patients with early AD (AD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…Patients with AD or MCI show increased CSF levels of α-syn[12, 17, 18], perhaps due to release from damaged neurons[40, 41], as has been hypothesized for the increased levels of CSF tau in AD. Fewer studies have examined α-syn across the transition from MCI to AD dementia; however, in one longitudinal study, CSF α-syn was higher in MCI subjects with a shorter duration of symptoms, but did not differ across diagnostic groups[42]. Here, we also find a significant difference in CSF α-syn levels between CN, AD and MCI.…”
Section: Discussionsupporting
confidence: 48%
“…Patients with AD or MCI show increased CSF levels of α-syn[12, 17, 18], perhaps due to release from damaged neurons[40, 41], as has been hypothesized for the increased levels of CSF tau in AD. Fewer studies have examined α-syn across the transition from MCI to AD dementia; however, in one longitudinal study, CSF α-syn was higher in MCI subjects with a shorter duration of symptoms, but did not differ across diagnostic groups[42]. Here, we also find a significant difference in CSF α-syn levels between CN, AD and MCI.…”
Section: Discussionsupporting
confidence: 48%
“…Especially in PD, α-synuclein interacts with tubulin, parkin, dopamine receptor, synphilin-1, phospholipase, and small ubiquitin related modifiers 20 . Previous studies showed that α-synuclein was not different between Apo e4 carriers and Apo e4 non-carriers in normal subjects, MCI, and AD, consistent with this study 22 , 23 . However, molecular linkage between Apo E and α-synuclein was demonstrated in one study using A30P and A53T transgenic mice.…”
Section: Discussionsupporting
confidence: 92%
“…The controversial results published in previous reports regarding the potential of CSF α‐syn as a diagnostic biomarker for AD and/or LBD (Spies et al ; Reesink et al ; Kapaki et al ; Berge et al ; Oeckl et al ) may be because of various factors like sample size, uncertain diagnosis and/ or uncontrolled follow‐up of patients or controls, patients enrolled at different stages of the disease, differences between the age of the groups, no control for blood contamination, and others. Analytical and methodological differences can also contribute to the mentioned discrepancies between reports, particularly derived from handling of the samples and lack of validated CSF α‐syn kits.…”
Section: Discussionmentioning
confidence: 98%
“…Cerebrospinal fluid (CSF) α‐syn levels have been studied in MCI and dementia disorders, but there is no consensus as to whether α‐syn is consistently affected (Spies et al ; Reesink et al ; Kapaki et al ; Toledo et al ; Korff et al ; Slaets et al ; Mackin et al ; Hansson et al ; Majbour et al ; Llorens et al ; Berge et al ; Oeckl et al ; Chiasserini et al ; Shi et al ; Wang et al ). Most published results indicated that CSF α‐syn, in combination with the ‘central core’ CSF biomarkers of AD, have clinical value in the differential diagnosis of AD and LBD at the stage of dementia (Slaets et al ; Shi et al ); and can be useful in diagnosing MCI due to AD (Korff et al ; Mackin et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation